Murs après murs : Les jeunes face aux politiques de rénovation urbaine - Solène Gaudin (Sociétés et Jeunesses en Difficulté)
Demolishing and rebuilding programs, heavily incited since the Borloo laws on 2003, brings on deep social and morphological transformations in delicate districts. As a result, the young population, whose doings and speeches reflect a very strong attachment to their living places, feel a supplementary kind of violence. How are these populations taken care of, and what society project is offered to them, so that they can build themselves? This analysis, consists in series of interviews made to both young and institutional actors in two Brittany districts, Brest and Lorient, who receive financial support from the national agency for urban restoration. If a part of these young people, often those who know the smallest difficulties, accept with a resignation feeling the projects offered to them, most of them express a feeling of rebellion and anger in front of what they consider an expropriation act. The quality of the proposed urban projects it is the capacity to master both their destiny and their private space that is here criticized.